Characterization of Dendritic Cells in the Human Female Genital Tract and their Role in HIV-1 Pathogenesis - Parthasarathy, Ragav Siddharth. (Tufts University. Tisch Library., 2025)
Thesis (Ph.D.)--Tufts University, 2024-12.; Submitted to the Dept. of Immunology.; Advisor: Marta Rodriguez-Garcia.; Committee: Pilar Alcaide, Shruti Sharma, and Alexander Poltorak.; Keyword: Immunology.